Joint universality of some zeta-functions. I - Račkauskienė, Santa; Šiaučiūnas, Darius (Lietuvos matematikos rinkinys, 2010)
In the paper, the joint universality for the Riemann zeta-function and a collection of periodic Hurwitz zeta functions is discussed and basic results are given.
Keywords: joint universality; limit theorem; periodic Hurwitz zeta-function; Riemann zeta function; space of analytic functions